Interpretation and Limitations of Projective Reading in the Poetic Poetry Text - Kadera , Ghithaa; Stite , Lara (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The interpretation of my reading art is based on the transition from the direct meaning in the apparent form to the indirect meaning in the implicit pattern, and verbal functions, images, and loaded structures are strongly suggestive. The critics of pre-Islamic poetry have enriched the old literature, adding to it the dimensions of literacy, and their interpretations of psychological meanings and profound semantics, indicating beyond the apparent textual levels, to various explanatory meanings, gave the textual poetry poetic content another poetry is the receipt. The interpretations of the critics presented a variety of purposes, based on the linguistic explanation, and the will of the poet at other times. The opinion of the reader and his convictions may intervene in this position, but they are interpretations, regardless of their degree of credibility or persuasion. They presented modern thought and opened up new texts. Jahili with a different vision.